Symptomatology associated with “Purple top”, an emerging disease of solanaceous fruit species - Viera, William; Viteri, Pablo; Cedeño, Diego; Garrido, Anita; Pachacama, Silvia; Gallo, Mónica (Revista Ceres, 2023)
“Purple top” is an emerging disease that affects solanaceous crops, reported mainly on Solanum tuberosum (potato). Additionally, Bactericera cockerelli has been reported as the insect vector of Candidatus Liberibacter solanacearum (CaLso), a pathogen that has been associated with this disease. However, the information about this disease in Andean fruit species such as Solanum betaceum (tree tomato), S. quitoense (naranjilla) and Physalis peruviana (cape gooseberry) is almost nil. This study was carried out in the Tumbaco Experimental Farm of INIAP to describe the phenotypic symptoms caused by this disease. Molecular diagnosis by PCR method was carried out to diagnose the causal agent associated with the symptomatology. The main symptoms observed were purple color leaves, smaller apical leaves, inward curvature edge leaves, over-sprouting, yellowish and stopped plant growth; however there also were asymptomatic plants. P. peruviana was the most susceptible species because showed 100% of incidence. CaLso was identified as the causal agent associated with this disease. These results contribute to understanding the expression of this disease in Andean fruit crops. However, more studies related to epidemiology, diagnostic methods, mixed infections, vector-pathogen interaction and disease control are required in order to generate information that allows a complete knowledge of this pest.